Pathways to reimagining commercial health insurance in India - Ashraf, Hasna; Ghosh, Indradeep; Kumar, Nishanth; Nambiar, Anjali; Prasad, Sowmini (Frontiers in Public Health, 2022)
In this paper we explore how India’s growing commercial health insurance (CHI) segment can be reformed to deliver adequate financial protection and good health outcomes. We lay out key issues in the demand- and supply-sides of the insurance market that need to be addressed for CHI to be more aligned towards universal health coverage (UHC). On the demand side, we identify a consumer who strays far from the rational actor paradigm and therefore one whose needs require a fundamentally different approach than the one that commercial health insurance in India has so far taken. We lay out precisely the different stages involved in bringing a consumer to the insurance market and the conditions under which that consumer is likely to purchase insurance. On the supply side, we describe the many concerns that a new entrant into the commercial health insurance market must grapple with. We conclude with a set of pathways that brings the two sides of the market together to shed light on possible pathways for reform in the commercial health insurance sector in India. Despite the many challenges that this sector faces in India, we believe that there is room for optimism, and with the right amount of regulatory foresight, even room for radical transformation.